2016
DOI: 10.1038/celldisc.2015.42
|View full text |Cite
|
Sign up to set email alerts
|

SMG7 is a critical regulator of p53 stability and function in DNA damage stress response

Abstract: The p53 tumor suppressor functions as a transcription factor and plays a pivotal role in regulation of cellular response to DNA damage by activating various genes including those involved in cell cycle arrest. p53 stability is essential for its function during stress response; however, the molecular mechanism for DNA damage-induced stabilization of p53 is not fully understood. In our present study, we have identified SMG7 (suppressor with morphological defects in genitalia 7), also known as EST1C, as a novel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…Whereas Tnfrsf1a mutant cells were partially resistant against Doxorubicin, Smg7 −/− cells showed only weak protection against this and other intrinsic inducers of apoptosis, demonstrating that global apoptosis is not inhibited per se. This is consistent with another report showing that Smg7 mutation does not increase survival against doxorubicin, but rather counterintuitively, transiently increases the fraction of early apoptotic cells [ 33 ]. However, Smg7 −/− cells showed resistance to Erastin at lower concentrations, suggesting that Erastin-induced ferroptotic cell death is multimodal and may be potentiated by the TNFa pathway.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Whereas Tnfrsf1a mutant cells were partially resistant against Doxorubicin, Smg7 −/− cells showed only weak protection against this and other intrinsic inducers of apoptosis, demonstrating that global apoptosis is not inhibited per se. This is consistent with another report showing that Smg7 mutation does not increase survival against doxorubicin, but rather counterintuitively, transiently increases the fraction of early apoptotic cells [ 33 ]. However, Smg7 −/− cells showed resistance to Erastin at lower concentrations, suggesting that Erastin-induced ferroptotic cell death is multimodal and may be potentiated by the TNFa pathway.…”
Section: Discussionsupporting
confidence: 93%
“…We also investigated the effect of TNFa treatment on core components of apoptosis in mutant cells. p53 (TRP53) is activated following DNA damage and SMG7 was recently reported to stabilize p53 following doxorubicin treatment [ 33 ]. We evaluated p53 levels in cells treated with TNFa and found that compared to the parental cell line Smg7 −/− cells showed a dramatic increase in p53 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SETDB1 is an oncogene in melanoma [54] and has also been found to be over-expressed in PCa and cell lines [55]. Further, we found genes involved in DNA damage repair, such as SMG7 [56] and ATR [57], and PRKCZ [58], which had already been suggested as a biomarker prognostic for survival in PCa [59].…”
Section: Effects Of Distinct Cnas Converge On Common Proteinssupporting
confidence: 56%
“…In our recent study, we show that the NMD factor SMG7 plays a critical role in the control of p53 protein stability following DNA damage 34 . Here, we investigate whether SMG7 can regulate p53 through the nonsense-mediated mRNA decay (NMD) pathway, as p53 isoforms β and γ are derived from alternative splicing of intron 9 and each contain a premature stop codon (PTC) before the last intron 3 , a common feature of NMD targets (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…NMD is carried out by a complex of RNA binding proteins, mainly the UPF1 ( re gulator of n onsense t ranscripts 1 (RENT1) 25 – 29 ) protein which is recruited to mRNA during translation if a premature termination codon (PTC) 20 , 30 , 31 is found and initiates recruitment of SMG ( s uppressor for m orphological effect on g enetalia) family proteins (SMG5, SMG6, and SMG7) and other cofactors to the mRNA for decapping, deadenyation, and ultimately mRNA decay 20 . SMG7, a critical NMD factor 32 , 33 , was shown by our group to be a novel regulator of p53α protein stability under DNA damage conditions 34 . Here, we sought to investigate whether SMG7 can regulate p53 via its NMD activity.…”
Section: Introductionmentioning
confidence: 99%